Santarcangelo, primi anni Novanta. Tracce di cyberpunk in teatro (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
The essay examines three experiences developed through the editions of the Santarcangelo Festival between the '80s and '90s led by Antonio Attisani under the project Lavoro d'arte comune (“shared artwork”) with the aim of opening both Italian theatre and the Festival to the new impulses that at that time were coming from different areas of artistic experimentation, cultural production, and social innovation: the work of Giacomo Verde, of the "Decoder" group and of the Mutoid Waste Com- pany, which ideally and then concretely converge in Santarcangelo between 1989 and 1993. The author studies these theoretical and practical twines in relation to the ideas that in the same period were arising in the context of the cyberpunk, in order to enlighten one of the important turning point through which in the '80s we can follow the transmission (and reworking) of the practices of artivism in Italian theatre, from the protests of the '60s and the '70s to the underground experiences of the new millennium.